2015
DOI: 10.1002/2015gl066082
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic model of earthquake clustering shows reduced stress drops for nearby aftershocks

Abstract: While a number of viable physical mechanisms have been offered to explain the temporal clustering of aftershocks, the spatial clustering of aftershocks, in particular the concentrated productivity of aftershocks very near the mainshock rupture area, has been difficult to reproduce with physical models. Here we present a new deterministic physical model capable of reproducing both the spatial and temporal clustering. We apply this new model to a longstanding puzzling question raised by ground motion observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Spatially varying stress drops may reflect strong fault heterogeneity [e.g., Fehler and Phillips , ], which for induced events may be influenced by the injection of fluids into the subsurface. Alternatively, low stress drops may be attributed to nearby aftershocks that re‐rupture parts of the mainshock fault plane that may not have completely healed [e.g., Vidale et al , ; Shaw et al , ]. It is unclear if the variation we observe here is a reflection of actual physical properties of the fault or simply due to scatter in the measurement due to changing station configuration and/or errors in corner frequency estimates.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Spatially varying stress drops may reflect strong fault heterogeneity [e.g., Fehler and Phillips , ], which for induced events may be influenced by the injection of fluids into the subsurface. Alternatively, low stress drops may be attributed to nearby aftershocks that re‐rupture parts of the mainshock fault plane that may not have completely healed [e.g., Vidale et al , ; Shaw et al , ]. It is unclear if the variation we observe here is a reflection of actual physical properties of the fault or simply due to scatter in the measurement due to changing station configuration and/or errors in corner frequency estimates.…”
Section: Discussionmentioning
confidence: 86%
“…Abercrombie [2014] reported that stress drops along the San Andreas Fault at Parkfield decrease following the 2006 M6.0 mainshock and then rebound rapidly to previous levels. She attributes the temporal variability to short recurrence time that limits healing time and may reflect lower fault strength [e.g., Vidale et al, 1994;Shaw et al, 2015]. Alternately, the apparent temporal correlation we observe here could simply reflect lateral or depth variability in the fault strength and changing event locations.…”
Section: 1002/2016jb013153mentioning
confidence: 93%
“…Similarly, stress drops for aftershocks in the 2007 M W 6.2 rupture asperity also decreased, suggesting these earthquakes occurred in the region of strong ground motion from the M W 6.0 mainshock. Low stress drop aftershocks (< 0.5 MPa) may reflect the rupture of fault segments that have not fully healed from the large earthquake ground motion (Shaw et al, ). In contrast, high stress drop (> 1 MPa) aftershocks may reflect strong asperities in a damaged and otherwise weakened fault zone (e.g., Dreger et al, ) or reflect stress concentrations at the fault edges (Oth & Kaiser, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is an ongoing debate in the literature regarding the frequency content of AS ground motions compared to MS ones [e.g. 17,18]. Nearby (to the MS rupture) ASs tend to exhibit lower stress drops compared to MS events with similar magnitude.…”
Section: Other Implicationsmentioning
confidence: 99%